Effects of Rice Husks on Yield and Tuber Quality of Potatoes(Solanum tuberosum L.) - Guler, Semiha (Asian Journal of Chemistry, 2010)
The present study was designed to investigate the effects of rice husks on yield and quality of potato (Sante cv.). In the study, 4 treatments including control (no fertilizer), farmyard manure (10 t/ha), rice husks (1 t/ha) and farmyard manure + rice husks (10 + 1 t/ha) were used. Total tuber yield, first class and third class tuber yield were significantly affected by treatments. First class tuber yield and total tuber yield were higher in farmyard manure, rice husks and farmyard manure + rice husks treatments when compared to control. In these treatments first class tuber yield and total tuber yield were ca. 29.8 and 28.2 % higher than control, respectively. In rice husks treatment, tuber yield, tuber number per plant and mean tuber weight were as high as in farmyard manure and farmyard manure + rice husks. There were no significant differences among treatments in dry matter content and bulk density of tuber. Whereas protein and ash content of tuber were significantly affected by treatments. This study showed that total and first class yield of potato increased with application of rice husks.